Opera in the development of German critical thought - Flaherty, Gloria, 1938-1992 (Princeton legacy library., 1978)
Although opera figured importantly in the French quarrel of the Ancients versus the Moderns and in the English discussions of heroic tragedy, it was in Germany that its role in the development of criticism and aesthetics was most pronounced. Beginning with this observation, Gloria Flaherty tries to show how, from its very inception and through most of its history, opera was related not only to the revival of ancient drama and the evolution of modern theater, but also to the development of modern critical thought. The author provides a comprehensive treatment of the writings both for and aga.